Aesthetic The Grand Mosque of Cimahi - Mulyana, Yusup; Fahmi, Rezza Fauzi Muhammad (Jurnal Riset Agama, 2023)
The Grand Mosque of Cimahi is the Cimahi city government mosque which is located in West Bandung Regency, West Java Province. The Grand Mosque of Cimahi has its own characteristics and uniqueness, this can be seen from the aesthetic value found in the interior aspects. Aesthetic values are analyzed with a semiotic review which is the focus of this research. The research process is carried out with field research and library research. Field research is carried out by directly visiting the research object. Library research was conducted to find and use sources from books, journal articles, and the writing of relevant scientific papers. The purpose of this research is to identify the visual elements, values, meaning, and aesthetics of The Grand Mosque of Cimahi. The method used in this research is the qualitative method. Observative steps are adjusted to related sources, and data contained in the research object can be described and analyzed. The importance of this is examined because The Grand Mosque of Cimahi is one of the historical pieces of evidence, then the mosque's unique interior form is due to its aesthetic and semiotic values. The results of this study that The Grand Mosque of Cimahi has an aesthetic of the interior filled with meaning.